2015
DOI: 10.1002/aic.15088
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different porous media on moisture loss and oil absorption profiles during frying using glass micromodels

Abstract: Microstructure plays a key role in oil absorption during frying. The aim of this work was to improve our understanding of the relationship between microstructure and oil absorption, through the use of glass micromodels to obtain evidence of transport phenomena in three porous networks. Micromodels were saturated with water and partially immersed in oil at 190°C. Moisture and oil profiles were imaged to get water and oil saturation maps. Image and fractal analyses were performed to describe the morphology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Similarly, the competition between oil and air transport to equilibrate the pressure inside the crust and deep inside the product cannot be captured with homogenized models. Detailed experiments showed that cellular defects with coordination numbers strictly larger than two (e.g., "Y" or "X" shapes) cause, indeed, complex displacements of oil and air phases (Cortés et al, 2016;Patsioura et al, 2015). As an illustration, the oil front is accelerated along the corners of parenchyma cells (acute angles) and usually reaches restrictions between cells faster than air.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the competition between oil and air transport to equilibrate the pressure inside the crust and deep inside the product cannot be captured with homogenized models. Detailed experiments showed that cellular defects with coordination numbers strictly larger than two (e.g., "Y" or "X" shapes) cause, indeed, complex displacements of oil and air phases (Cortés et al, 2016;Patsioura et al, 2015). As an illustration, the oil front is accelerated along the corners of parenchyma cells (acute angles) and usually reaches restrictions between cells faster than air.…”
Section: Introductionmentioning
confidence: 99%
“…Varios factores que afectan la absorción de grasa (AG) han sido reportados, entre los que se destacan algunos propios de las matrices alimentarias como la composición química, humedad inicial y la porosidad (Moreno y Bouchon 2013; Cortés et al 2016;Zhang et al 2016). Asimismo, otros asociados a las condiciones del proceso como el tiempo, temperatura, la presión, tensión superficial alimento/grasa, el tipo de grasa y su viscosidad (Bouchon 2009; Albertos et al 2016).…”
Section: …………………………………………………………………………………………………… Introducción:-unclassified
“…Entendimiento de la AG:-En la actualidad los mecanismos involucrados en el proceso de AG durante la fritura por inmersión continúan siendo estudiados (Cortés et al 2016;Zhang et al 2016). Diversos autores han reportado que la cinética de AG por parte de los productos alimenticios es compleja; ya que mientras el vapor esté presente en los poros del alimento, impedirá el ingreso del aceite al interior del mismo, es decir, la absorción está limitada durante el periodo de inmersión y sólo cuando el alimento es retirado de la freidora y empieza el enfriamiento, la presión del vapor disminuye y se produce un efecto de succión (vacío), ayudando a que el aceite depositado en la superficie pueda atravesar la costra.…”
unclassified